Meta-analysis: The effect of guided inquiry on students' critical thinking skills in biology learning - Dewi Asriani Ridzal; Mujuna Hatuala; Haswan Haswan; Farnia Farnia (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Critical thinking skills are one of the six skills (6C) that must have by students to face competition in the 21st century. Guided inquiry is one of the learning models that can be used to increase students' critical thinking skills in biology learning. The purpose of the study was to determine the effectiveness of the enforcement of the guided inquiry model, especially on students' critical thinking skills in biology learning based on the effect size value in terms of education level. This research method is a meta-analysis method. The research sample taken from 12 national articles consists of seven journals at the high school level and five journals at the junior high school level. The results showed that the guided inquiry model was effectively used both at the high school and junior high school levels because it was proven to have a forceful impact on students' critical thinking skills in biology learning with an average effect size value of 1.651 (strong effect). Based on the level of education, the enforcement of the guided inquiry model at the high school level has a higher impact on student's critical thinking skills with an effect size value of 1.866 (strong effect) than at the junior high school level with an effect size value of 1.435 (strong effect). This guided inquiry model needs to be applied more broadly so that more students have critical thinking skills and ready to compete in the global world.Abstrak Keterampilan berpikir kritis merupakan salah satu dari 6 kecakapan (6C) yang harus dimiliki oleh siswa agar dapat menghadapi persaingan di abad 21. Inkuiri terbimbing menjadi salah satu model pembelajaran yang dapat digunakan untuk meningkatkan keterampilan berpikir kritis siswa pada pembelajaran biologi. Tujuan penelitian adalah untuk mengetahui efektivitas penerapan model inkuiri terbimbing khususnya terhadap keterampilan berpikir kritis siswa pada pembelajaran biologi berdasarkan nilai besarnya efek ditinjau dari jenjang pendidikan. Jenis penelitian ini adalah meta analisis. Sampel penelitian terdiri dari 12 artikel yang terdiri dari 7 jurnal pada jenjang SMA dan 5 jurnal pada jenjang SMP. Hasil penelitian menunjukkan model inkuiri terbimbing efektif digunakan baik pada jenjang SMA maupun SMP karena terbukti dapat memberikan pengaruh yang sangat kuat terhadap keterampilan berpikir kritis siswa pada pembelajaran biologi dengan nilai rerata besaran efek sebesar 1.651 (efek kuat). Berdasarkan jenjang pendidikan, penerapan model inquiry terbimbing pada tingkat SMA memiliki pengaruh yang lebih besar terhadap keterampilan berpikir kritis siswa dengan nilai besaran efek sebesar 1.866 (efek kuat) dibanding ditingkat SMP dengan nilai besaran efek sebesar 1.435 (efek kuat). Model inkuiri terbimbing ini perlu diterapkan secara lebih luas agar lebih banyak peserta didik yang memiliki keterampilan berpikir kritis dan siap bersaing di dunia global.